2013
DOI: 10.1257/app.5.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Development Effects of Electrification: Evidence from the Topographic Placement of Hydropower Plants in Brazil

Abstract: We estimate the development effects of electrification across Brazil over the period 1960–2000. We simulate a time series of hypothetical electricity grids for Brazil for the period 1960–2000 that show how the grid would have evolved had infrastructure investments been made based solely on geography-based cost considerations. Using the model as an instrument, we document large positive effects of electrification on development that are underestimated when one fails to account for endogenous targeting. Broad-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(198 citation statements)
references
References 14 publications
7
176
0
1
Order By: Relevance
“…Studies have found effects of access to electrification on a wealth of socioeconomic variables like employment (Dinkelman, 2011), indoor air quality (Barron and Torero, 2015a), energy use, time allocation, and income (Barron and Torero, 2015b;Bensch, Kluve, and Peters, 2010;Khandker, Barnes, andSamad, 2012, 2013;Chakravorty, Pelli, and Marchand, 2013), housing value and human development (Lipscomb, Mobarak, and Barham, 2013). However, there is still scarce evidence on the role that access to electricity plays on firm performance and industry development, two key elements of economic growth.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Studies have found effects of access to electrification on a wealth of socioeconomic variables like employment (Dinkelman, 2011), indoor air quality (Barron and Torero, 2015a), energy use, time allocation, and income (Barron and Torero, 2015b;Bensch, Kluve, and Peters, 2010;Khandker, Barnes, andSamad, 2012, 2013;Chakravorty, Pelli, and Marchand, 2013), housing value and human development (Lipscomb, Mobarak, and Barham, 2013). However, there is still scarce evidence on the role that access to electricity plays on firm performance and industry development, two key elements of economic growth.…”
Section: Manuel Barronmentioning
confidence: 99%
“…It has been estimated that around a quarter of the world's population lack access to electricity. Lipscomb et al (2013) study the long-run effects of electrification in Brazil: using spatial variation in the scope for hydropower plants, they can isolate exogenous variation in the extension of the network. Their results suggest that electrification brings significant gains in educational attainment, employment rates and income per capita.…”
Section: Transport and Infrastructurementioning
confidence: 99%
“…Another study by Lipscomb et al (2011) studies development effects of electrification between 1960 and 2000 using geological placement of hydropower plants in Brazil. Elec-trification is most probably correlated with unobservable effects like political decisions and other demand side concerns.…”
Section: Introductionmentioning
confidence: 99%